2003
DOI: 10.1055/s-2003-40867
|View full text |Cite
|
Sign up to set email alerts
|

4-Dimethylamino-pyridine(DMAP)

Abstract: This feature focuses on a reagent chosen by a postgraduate, highlighting the uses and preparation of the reagent in current research SPOTLIGHT 1568 4-Dimethylamino-pyridine (DMAP)Compiled by Christoph Grondal Christoph Grondal (1979) studied chemistry at the FriedrichWilhelms University of Bonn. Currently, he is carrying out his diploma thesis on application of functionalized cyclohexadienes in diversity oriented synthesis in the research group of Michael Müller at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Thus, bicyclic compound 16 and azajulolidine (5) demonstrated their powerful acylation properties. [18] Later on, Han experimentally confirmed the optimal situation brought about by 6,6-appended cycles (see Table 2 with compounds 5, [16][17][18][19][20]. [38] It should be added that kinetic data reported for electron-rich catalysts, such as 5, are quite sensitive to the protocols used for their synthesis, purification and rate [a] In all cases s N is 0.67 save that of NMe 2 which is 0.66.…”
Section: -Aminopyridinesmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, bicyclic compound 16 and azajulolidine (5) demonstrated their powerful acylation properties. [18] Later on, Han experimentally confirmed the optimal situation brought about by 6,6-appended cycles (see Table 2 with compounds 5, [16][17][18][19][20]. [38] It should be added that kinetic data reported for electron-rich catalysts, such as 5, are quite sensitive to the protocols used for their synthesis, purification and rate [a] In all cases s N is 0.67 save that of NMe 2 which is 0.66.…”
Section: -Aminopyridinesmentioning
confidence: 94%
“…Commercial availability of DMAP and PPY as early as 1979 stimulated their popular use, and innovation was only directed toward investigation of chiral derivatives for enantioselective trans-formations. [14] As a result, until 2003, successive reviews, [15][16][17] were tacitly accepting the idea of a limit of reactivity reached with PPY. It fell to Steglich, the author of the above-cited definitive sentence, to contradict and to demonstrate that conformational lock of the dialkylamino moiety could further increase the catalytic activity of PPY.…”
Section: Dmap and Its Derivativesmentioning
confidence: 99%
“…4‐(Dimethylamino)pyridine (4‐DMAP, 1 ) is well known as a catalyst for the esterification of alcohols by acid anhydrides and for various other synthetically useful transformations involving acyl transfer 1. 2 Its catalytic potential was first discovered by the groups of Litvinenko and Steglich in the late 1960s3, 4 and its synthetic utility and that of its congeners, including polymeric variants,5 have been reviewed 69.…”
Section: Methodsmentioning
confidence: 99%
“…4-DMAP is produced by the chemical industry discharging via the WWTP, is used as nucleophilic catalyst in industrial processes (Grondal, 2003), but was reported as not mutagenic (Ogawa et al, 1988). An ethoxy(pyrrolidinyl)benzaldehyde and 2-ethoxy-N-(1-methyl-3-phenylpropyl)-acetamide were tentatively identified based on matching predicted and experimental retention times and HRMS/MS information.…”
Section: Analysis Of the Peaks Detected As Co-varying With Mutagenic mentioning
confidence: 99%